Academic Autonomy of Private Universities Under Thai Law - Maneesuwan, Khemmarat (Chalermkarnchana Academic Journal, 2025)
Academic freedom is a fundamental principle that allows higher education institutions to conduct teaching and research without undue interference. However, private universities in Thailand face legal and administrative constraints that may impact the academic freedom of faculty members and researchers. This study examines the legal issues related to academic freedom in private universities under Thai law by analyzing existing laws, government policies, and university practices. The findings reveal that Thai legal frameworks impose several restrictions on curriculum development, research autonomy, and academic expression. Additionally, the commercial-oriented management structures of private universities may hinder the independence of academic staff. The study highlights the need for legal and policy reforms to balance state regulation with the academic freedom of private universities